(untitled) (Deutscher Suchtkongress, 2023)
Hintergrund und Fragestellung From adolescence to young adulthood to middle age, alcohol consumption (AC) varies across the lifespan. Here we show that the magnitude of the association of psychosocial variables predictive of AC and alcohol use disorder (AUD) varies as a function of age and gender. Methoden We examined the cross-sectional association of four psychosocial correlates (impulsiveness, stress, depression, and loneliness) of AC in 601 subjects (234 women and 367 men; aged 37.9 years ± 12.9 years; range 17 to 66 years) suffering from AUD from the TRR 265 cohort, controlling also for cognitive status (i.e., digit-symbol substitution). Due to collinearity of stress and depression, these two variables were transformed to their two principal components (indicating stress and depression versus coping). Ergebnisse Specifically, we hypothesized and found impulsiveness to exhibit stronger associations in and young adults; for men the strong association also extended to early middle-aged adults. Likewise, the hypothesized effect of stress and depression significantly interacted with age and gender: for men, higher levels of stress and depression were associated with an increase of alcohol consumption, but this association decreased with age. For women, higher levels of stress and depression were associated with increased alcohol consumption only in late, but not in middle-age, and stress and depression were associated with decreased alcohol consumption in adolescent and young women. Diskussion und Schlussfolgerung The prominent age- and gender related differences in psychosocial predictors of AC reveal that different behavioral mechanisms contribute to AC in men and women at different ages. Further research is needed to delineate the temporal dynamics of these predictor sets. Our results will directly inform more targeted preventive interventions in men and women of different age groups in the framework of the ReCoDe consortium. Offenlegung von Interessenskonflikten sowie Förderungen Ich und die Koautorinnen und Koautoren erklären, dass während der letzten 3 Jahre keine wirtschaftlichen Vorteile oder persönlichen Verbindungen bestanden, die die Arbeit zum eingereichten Abstract beeinflusst haben könnten. Erklärung zur Finanzierung: DFG